The national question and electoral politics in Quebec and Scotland - Bélanger, Éric; Nadeau, Richard, 1956-; Henderson, Ailsa; Hepburn, Eve (Democracy, diversity, and citizen engagement series, 2018)
A comprehensive look at the intricacies of issue voting in substate nations.